Corporate governance and employee power in the boardroom: An applied game theoretical analysis - Benjamin Balsmeier; Andreas Bermig; Alexander Dilger; Hannah Geyer (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2011)
The discussion about employee representation on supervisory boards has received much attention from scholars and politicians around the world. We provide new insights to this ongoing debate by employing power indices from game theory to examine the real power of employees on boards and its effect on firm performance. Based on unique panel data of the largest listed companies in Germany, we find an inversely U-shaped relationship between labour power and Tobin's Q with a value-maximising labour power of approximately 43 %. Our results are robust to different game theoretical calculations of labour power, as well as various econometric models. – – Die Diskussion über Arbeitnehmermitbestimmung in Aufsichtsräten hat erhebliche Aufmerksamkeit von Wissenschaftlern und Politiker in vielen Ländern erfahren. Wir tragen neue Einsichten zu dieser fortdauernden Debatte bei, indem wir spieltheoretische Machtindices verwenden, um die Macht von Beschäftigten und deren Beitrag zum Unternehmenserfolg zu bestimmen. Mit originären Paneldaten der größten deutschen gelisteten Unternehmen finden wir eine umgekehrt U-förmige Beziehung zwischen Arbeitnehmermacht und Tobin's Q, wobei die wertmaximierende Arbeitnehmermacht bei rund 43 % liegt. Unsere Ergebnisse sind robust sowohl hinsichtlich unterschiedlicher spieltheoretischer Berechnungen der Arbeitnehmermacht als auch verschiedener ökonometrischer Modellierungen.
Keywords: C71; D72; J53; K22; K31; L21; L25; M21; M54; 330